Accounting Irrelevance: Dimensi Affect Heuristic pada Formulasi Harga Jual Badan Usaha Retail - ., Karina; Pontjoharyo, Wiyono (Jurnal Riset Akuntansi dan Keuangan, 2021)
People often receive more information when they learn from their past. Past experience and belief may be particularly powerful in influencing judgments. Uniqueness of an object often leads to specific valuation. This unique object can be measured with special valuation techniques, including affect heuristic. Coupled with experience and belief, affect heuristic gives information that is easy to access in valuation activity. This explanatory research explains the role of affect heuristic in pricing electronic products as one of conventional goods. Using phenomenological approach, this qualitative research aims to gain better understanding of lived mindset and experience from price makers in pricing activity. This research finds some limitations that must have contributed to accounting irrelevance in pricing activity.